There are two ways to solve this question.
1) To solve this question, we need to substitute a = 6 and b = -3 into the given expression and then evaluate:
(-a)(b)(-a + b)
= (-6)(-3)(-6 + (-3))
= 18(-9)
= -162
2) An alternative method is to simplify (-a)(b)(-a + b) into an expression without brackets and then substitute a = 6 and b = -3:
1. (-a)(b)(-a + b)
= (-ab)(-a + b)
= -ab*(-a) + (-ab)*b
= a^(2)b+ (-ab^(2))
= a^(2)b - ab^(2)
2. a^(2)b - ab^(2)
= 6^(2)*(-3) - 6*(-3)^2
= 36*(-3) - 6*9
= -108 - 54
= -162
The key to either method is to be careful with placement of brackets, especially where there are negative values involved.